Method of universal algebra construction for image processing - Vorobel, Roman (Видавництво Львівської політехніки, 2010)
New universal algebra and method for its construction is described. Operations of addition and multiplication by real scalar are defined for interval (-M, M), where M>0. New algebra generalizes known algebraic structures of Jourlin-Pinoli and Patrascu. The using of triangular norms and the laws of human visual system (HVS) is the base of proposed approach.
Keywords: logarithmic image processing; abstract linear algebra; vector space; image enhancement; HVS